Small business advantage - Encore Software (Firm) (Los Angeles : Encore Software Inc, 1998)
"6 powerful and essential tools which will have a dramatic impact in your business
Legal advisor -- Business and marketing plan -- Credit manager -- Reports and forms -- Sales and marketing -- Raising money
System requirements: IBM compatible PC (486 DX2 or greater); 8 MB of RAM (12 MB recommended); Windows 3.1 or higher; 2X CD-ROM drive and Sound Blaster sound card
Keywords: Small business -- Planning; Business planning; Marketing planning; Credit management; Computer software; CD-ROMs.